2011
DOI: 10.1007/s10753-011-9361-1
|View full text |Cite
|
Sign up to set email alerts
|

Association Between C-Reactive Protein and Type 2 Diabetes in a Tunisian Population

Abstract: The aim of this study was to investigate the association of CRP levels with type 2 diabetes (T2D) and its related variables in a sample of the Tunisian population. Our sample included 129 patients with T2D and 187 control subjects. Body mass index (BMI), plasma lipids, glucose, insulin, and CRP concentrations were measured for each participant. Homeostasis model assessment of insulin resistance (HOMA-IR) was calculated. T2D was defined as a fasting plasma glucose (FPG) level ≥ 7.0 mmol/L, the use of anti-diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
(56 reference statements)
4
15
0
Order By: Relevance
“…The link between CRP and diabetes has been widely reported [5, 6]. We found that the pre-diabetic and T2DM groups had markedly higher CRP levels than the normal group.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The link between CRP and diabetes has been widely reported [5, 6]. We found that the pre-diabetic and T2DM groups had markedly higher CRP levels than the normal group.…”
Section: Discussionsupporting
confidence: 57%
“…Elevation of CRP was related to an increased risk of developing T2DM [5, 6] and was suggested as an independent risk determinant for newly diagnosed T2DM [7, 8]. However, these results are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in keeping with those of Belfki et al [50] who demonstrated that levels of CRP are significantly elevated in patients with T2DM versus controls. Morohoshi et al [51] and Guha et al [52] mentioned that hyperglycemia stimulates the liberation of the inflammatory cytokine such as IL-6 and TNF-α from different cell types and results in the secretion of acute phase reactants by adipocytes.…”
Section: Discussionsupporting
confidence: 92%
“…A total of 46 T2D patients were recruited in the study through outpatient clinics of Dasman Diabetes Institute, Kuwait. T2D was defined as a fasting plasma glucose level of ≥7.0 mmol/L and use of anti-diabetic drugs [27]. Those with serious morbidities including pulmonary, renal, hepatic, cardiovascular, hematologic or immune diseases, type-1 diabetes, pregnancy, or malignancy were excluded.…”
Section: Subjects Anthropometric Measurements and Clinical Assaysmentioning
confidence: 99%